Electrical deterioration of 4H-SiC MOS capacitors due to bulk and interface traps induced by proton irradiation. (March 2023) - Lin, Ya-Xun; Chao, Der-Sheng; Liang, Jenq-Horng; Jiang, Jheng-Yi; Huang, Chih-Fang
Abstract: In this study, the displacement damage dose (DDD) effects of proton irradiation on bulk crystal and interfacial properties of 4H-SiC MOS capacitors (MOSCs) were investigated. The Monte Carlo calculation code named SRIM (Stopping and Range of Ions in Matter) was first used to predict the depth profiles and damage distributions of protons. The 4H-SiC MOSCs were irradiated with 60, 100, 150 keV protons to fluences ranging from 5 × 10 11 to 5 × 10 13  cm −2 . Capacitance-voltage (C-V) curves of the MOSCs were then measured to characterize the variation of the electrically active defects in 4H-SiC MOSCs. The results revealed that the non-ionization energy loss of incident protons leads to the accumulation of the primary defects in bulk SiC crystal as well as the increase of the interface traps between SiO2 and SiC crystal. A distinctive bump phenomenon was found in the weak inversion region of the C-V curve and it became more prominent with the increase of proton fluence, providing evidence for the existence of bulk traps. Furthermore, the incident proton energy is also a crucial factor in interface deterioration, suggesting that more interface traps would be formed when the proton damage peak is closer to the SiO2 /SiC interface. Highlights: Displacement damage effects of proton irradiation on 4H-SiC MOSCs were investigated. Non-ionization energy loss of protons leads to the buildup of bulk and interface traps. A distinctive bump in weak inversion region of CV curve implies the existence of bulk traps. Lowering proton incident energy accelerates the interface deterioration of SiC MOSCs.